TINJAUAN HUKUM INTERNASIONAL TERHADAP DIPLOMAT YANG MELAKUKAN TINDAKAN MELAWAN HUKUM DIHUBUNGKAN KEKEBALAN DIPLOMATIK - Ali Sentosa; Sutiarnoto Sutiarnoto; Jelly Leviza (Journal of USU International Law, 2013)
ABSTRACT A country needs to make contact with each other based on the national interests of each country are related to each other, among others, include the economic, social, cultural, legal, political, and so forth. With an association constant and continuous between the nations of the world, is one of the conditions of the existence of the international community. One form of cooperation between the countries in the world is in the form of international relations by putting diplomatic representatives in various countries. These representatives have the right diplomatic immunity and privileges of diplomatic immunity to the law of the jurisdiction of the receiving country as well as both civil and criminal immunity to witnesses. Thesis writing, entitled Review of International Law Against Diplomat Conducting Illegal Actions Associated with Diplomatic Immunity elaborated on how the law on abuse of diplomatic immunity, how the actions of a country against the abuse of diplomatic immunity and how the analysis of several cases of abuse of diplomatic immunity. To answer the problems that used normative law through the use of secondary data, such as books, legislation, books on financing agreements, and research results related to this research topic. Based on the results of the study explained that cases of violation of diplomatic relations that occurred in the period 1961 until now is the number of violations were related to the personal immunity of diplomatic missions and diplomatic representatives of the building violations. Some cases such as wiretap News Agency of the Republic of Indonesia (Embassy) in Myanmar and the case of slavery which made the German Ambassador to Indonesia citizens in Saudi Arabia became a serious concern. The existence of diplomatic immunity is considered as a protection to the perpetrators go unpunished. Action against abuse of diplomatic immunity recipient country can do eviction or persona non grata on diplomatic missions, in which it set in the Vienna Convention in 1961. Actions taken by one country against the abuse of diplomatic immunity is a form of action against the self-expulsion of the foreign diplomatic representatives. This is because of the immunity rights inherent in every foreign diplomatic representatives.